A turn-on mitochondria-targeted fluorescent probe for detecting and imaging hydrogen peroxide in vitro and in vivo. (August 2022) - Xu, Jia-Qi; Guo, Jin-Shuang; Xie, Ke-Feng; Gao, Meng-Jiao; Wei, Ran; Xin, Zhen-Hui; Kang, Yan-Fei
Abstract: In this work, we designed and synthesized a turn-on fluorescent probe for detecting H2 O2 . The results demonstrated that probe JQ-1 exhibited a high selectivity for H2 O2 . In addition, probe JQ-1 exhibited excellent sensitivity (detection limit: 87 nM) and a fast response time (∼10 min). Organelle co-localization experiment showed that JQ-1 mainly targeted mitochondria, which provided possibility to detect change of H2 O2 level in mitochondria. JQ-1 can be used to image exogenous and endogenous H2 O2 in vitro and vivo. Meanwhile, we used JQ-1 as fluorescence dye to investigate the change of H2 O2 level during immunogenic cell death for the first time by confocal laser scanning microscopy and flow cytometry, and the results showed that H2 O2 level had negligible change in process. Therefore, the results suggested that this probe is a reliable chemical tool for monitoring both endogenous and exogenous H2 O2 . Graphical abstract: In this work, we designed and synthesized a localized mitochondrial probe, which showed excellent selectivity and anti-interference capability. The detection limit of 87 nM and reaction time of 10 min provided the advantage for real-time detection of H2 O2 in practical application. In addition, the probe can image exogenous and endogenous H2 O2 in vitro and vivo. Image 1 Highlights: Low detection limit (87 nM) and a fast response time (∼10 min). The probe has mitochondrial targeting capability. There was an excellent linear relationship between fluorescence intensity and H2 O2 concentration with 0–50 μM. The probe is able to visualize exogenous and endogenous H2 O2 in living Hela cells and zebrafish.